Differentially displayed expressed sequence tags in Melipona scutellaris (Hymenoptera, Apidae, Meliponini) development - Santana,Flávia A. (2006)
We have compared gene expression, using the Differential Display Reverse Transcriptase - Polymerase Chain Reaction (DDRT-PCR) technique, by means of mRNA profile in Melipona scutellaris during ontogenetic postembryonic development, in adult worker, and in both Natural and Juvenile Hormone III-induced adult queen. Six, out of the nine ESTs described here, presented differentially expressed in the phases L1 or L2, or even in both of them, suggesting that key mechanisms to the development of Melipona scutellaris are regulated in these stages. The combination HT11G-AP05 revealed in L1 and L2 a product which matches to thioredoxin reductase protein domain in the Clostridium sporogenes, an important protein during cellular oxidoreduction processes. This study represents the first molecular evidence of differential gene expression profiles toward a description of the genetic developmental traits in the genus Melipona.